Seventh Annual National Two-Way Bilingual Immersion Summer Conference 1999
A program for the conference Staying the Course-Two-Way Bilingual Immersion in a Sea of Change hosted at the Monterey Conference Center at the Doubletree Hotel, Monterey, California.